The Ease of Data Sales Visualization Using The Interactive Tableau Dashboard to Support Decision Making in MSMEs - Darajuanti, Rafini; Purnama Sari, Ratna; Budiarto, Dekeng Setyo (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2025)
Micro, small, and medium enterprises (MSMEs) face the challenge of surviving and competing with other MSMEs and other higher forms of corporations, which need a very fast and rapid decision-making process. This study aims to implement digital transformation, especially in MSMEs, by using an interactive dashboard called Tableau. This research was conducted in Vifas Batik Yogyakarta and used interviews, observations, and documentation to gather the data. This research also goes through some process from designing and implementation itself. Due to the implementation process, it can be concluded that the use of an interactive dashboard can easily and quickly help business owners to know their business performance better. This research also provides practical contributions for other MSMEs with similar issues and adds to the accounting information system literature about the implementation of business intelligence towards MSMEs' decision-making processes.